Evaluation of lysis filtration as an adjunct to conventional blood culture. Issue 1 (January 1986) - Chan, R; Munro, R; Tomlinson, P
Abstract : A lysis filtration system was used in conjunction with conventional broth culture for 1112 blood cultures. The system, which entailed collection of 5 ml of blood into bottles containing 50 ml isotonic phosphate buffer, Tween 20, and Rhozyme with subsequent filtration using a 0.45 micron Millipore field monitor, was simple and economical to use. Positive results were obtained earlier than those obtained with conventional broth cultures, and almost twice as many fungi and yeasts were isolated. Some fastidious organisms such as Haemophilus influenzae and Streptococcus pneumoniae however, were not recovered from the lysis system, and contaminants in lysis cultures were three times as common as in conventional culture. The number of positive cultures was also adversely influenced by incubation of the blood lysis mixture overnight before filtration. We conclude that this lysis filtration system is useful as an adjunct to conventional broth culture in selected patients in cases in which filtration can be carried out soon after collection.